2017
DOI: 10.7324/rjc.2017.1041910
|View full text |Cite
|
Sign up to set email alerts
|

"Experimental Analysis on Reinforced Aluminium Metal Matrix With Boron Carbide, Graphite and Fly Ash Chemical Composites "

Abstract: The objective of this research is to perform an experimental study on the tribological behavior of Al-7075 alloy reinforced with boron carbide (B4C), graphite (Gr) and fly ash. The reinforcements added to aluminium alloy in three different compositions like B4C at 3wt%/Gr at 3wt%/ fly ash at 6wt%, B4C at 3wt%/Gr at 4wt%/ fly ash at 7wt% and B4C at 3wt%/Gr at 5wt%/ fly ash at 8wt%. The composites were fabricated through stir casting process. Hardness and wear tests were conducted for all three different composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…SiC particle reinforced with aluminum matrix composite (AMC) with different particle weight fraction of 5, 7 and 10% were prepared and it was found that the hardness and toughness increased by 1.84 and 2.16 times respectively with particles weight fraction of 10%. The finding was that, the mechanical properties of the composite, improved mainly due to the high hardness of silicon carbide particles [23][24][25][26][27]. Study about the microstructures, mechanical properties and wear characteristics of SiC reinforced AMCs by varying contents of 0, 5, 10 and 20 wt.…”
Section: Literature Reviewmentioning
confidence: 99%
“…SiC particle reinforced with aluminum matrix composite (AMC) with different particle weight fraction of 5, 7 and 10% were prepared and it was found that the hardness and toughness increased by 1.84 and 2.16 times respectively with particles weight fraction of 10%. The finding was that, the mechanical properties of the composite, improved mainly due to the high hardness of silicon carbide particles [23][24][25][26][27]. Study about the microstructures, mechanical properties and wear characteristics of SiC reinforced AMCs by varying contents of 0, 5, 10 and 20 wt.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cart springs were molded using 20% short, long glass fiber reinforced polypropylene as well as unreinforced polypropylene and evaluated for the joint strength. Tested joints were subjected to completely reversed fatigue loads, wherein long fiber reinforced cart spring joint exhibited superior performance at high cycle fatigue conditions than that of short fiber reinforced and unreinforced polypropylene cart spring joints [17][18][19][20]. Design and structural analysis of composite cart spring made of glass fiber reinforced polymer was carried out.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With a 7-micron SiC size demonstrating a tensile strength of 428 MPa, 98 GPa Young's modulus, and a ductility of 8.5%, their work showed a notable improvement in tensile characteristics. S Nallusamy et al [17] study on the tribological behavior of Al-7075 alloy reinforced with boron carbide (B4C), graphite (Gr), and fly ash revealed promising results. Three different compositions were examined, namely B4C at 3wt%/Gr at 5wt%/fly ash at 8wt%, along with two other compositions.…”
Section: Introductionmentioning
confidence: 99%